Opening-up or closing-down climate deliberations: comparing the Climate Assembly UK and French Convention Citoyenne pour le Climat - Christina Demski; Catherine Cherry; Stuart Capstick; Caroline Verfuerth; Claire Mellier (Environmental Research Communications)
Climate change is among the most complex problems facing societies, with far-reaching implications for the structure of economies to everyday life. There is no one way to meet carbon targets but decisions on how to do so have, so far, mostly involved politicians and experts. Climate assemblies (CAs) are attempting to give citizens a more direct role in decision-making. There is hope that by engaging more deeply with public perspectives, climate policies could be more ambitious, just, and effective. Existing research has shown that the ways in which CAs are designed has an important influence on their outcomes. This paper contributes to this literature by examining how the recommendations of CAs are influenced by the design of the deliberations, as well as the overall scope and remit of the process. We use two case studies–the Climate Assembly UK (CAUK) and the French Convention Citoyenne pour le Climat (CCC), combining our own observations from attending both processes with analysis of openly available materials. We discuss the extent to which the CAUK and CCC could be considered opening-up or closing-down deliberations and what this means for the way they represent public perspectives on climate policy. We find that both CAs had relatively closed framings around a specific policy target, but the CCC avoids the overly technical framing of climate change, by also including elements of urgency and social justice. The CAUK used a predominantly top-down approach to deliberations whereby the structure of process strongly privileged expert opinion within discussions and recommendations. The CCC used a much more bottom-up approach with recommendations being iteratively developed by citizens. Both processes struggled to engage with more systemic and transformative issues. These insights are important for those designing CAs as well as those who hope to understand more about public preferences on climate policies.